Precise patterning of single crystal arrays of organic semiconductors by a patterned microchannel dip-coating method for organic field-effect transistors. Issue 15 (6th April 2021) - Wang, Chaoqiang; Lu, Zhengjun; Deng, Wei; Zhao, Wanqin; Lu, Bei; Xiao, Jie; Zhang, Xiujuan; Jie, Jiansheng; Zhang, Xiaohong
Abstract : A patterned microchannel dip-coating method was developed for achieving high-quality organic single crystal arrays, ensuring the fabrication of discrete organic field-effect transistor arrays with a high average mobility of 1.5 cm 2 V −1 s −1 . Abstract : Control over the growth location and orientation of organic semiconductor single crystals (OSSCs) is of key importance to enable high-performance organic circuits. However, it is difficult to create well-patterned and aligned OSSCs simultaneously using previous approaches. In this work, we demonstrate a patterned microchannel dip-coating (PMDC) method for the patterning of OSSC arrays with high crystallinity and purely crystallographic orientation. The patterned microchannels provide regionally different wettability, permitting to define solution wetting locations. Moreover, the dip-coating process enables unidirectional dewetting of the solution, inducing a long-range ordered crystallization. The PMDC approach shows a good universality, and can be extended to a variety of soluble acenes, e.g. 2, 8-difluoro-5, 11-bis(triethylsilylethynyl)anthradithiophene (Dif-TES-ADT) and 6, 13-bis(triisopropylsilylethynyl)pentacene (TIPS-pentacene). 50 discrete organic field-effect transistors (OFETs) made from the patterned Dif-TES-ADT single crystal arrays exhibit a high average mobility up to 1.5 cm 2 V −1 s −1, surpassing that of the commonly used amorphous silicon transistors. This patterning approach constitutes a promising step that might ultimately allow us to use high-mobility OSSCs for integrated devices.